Engineering practice of underground heat injection-enhanced gas extraction in low-permeability coal seams. Issue 3 (14th September 2022) - Hu, Linjie; Feng, Zengchao; Zhou, Dong; Wang, Xing; Zhao, Dong
ABSTRACT: The heat injection mechanism for improving gas desorption, coal seam gas pressure, and coal seam permeability in the Yangquan mining area was investigated via theoretical analysis. This analysis was conducted to address the problems of poor permeability, difficult gas extraction, and low extraction efficiency of 15# coal seam. An underground heat injection-enhanced gas extraction technology was proposed; accordingly, a heat injection-enhanced gas extraction system was developed and appropriate extraction methods were devised. The findings of an industrial test on 15# coal seam in the coal mine show that the proposed technology not only increased the amount of gas extracted but also halved the extraction time and realized efficient gas extraction. Two mature underground heat injection-enhanced gas extraction methods were established. These methods have similar gas production principles in that the gas production speed and gas concentration in the heat injection stage are relatively low, while the average degree of improvement in the extraction stage after heat injection can reach more than 50 times. The average degree of improvement in gas production speed and gas concentration after the second heat injection is greater than that after the first.